Teachers Personality on Students’ Motivation in Learning English - Saiful, Saiful (Institut Agama Islam Negeri Palopo, 2023)
This study aims to determine the effects of a teacher's personality on third-grade pupils at SMPN 3 Pallangga's motivation to learn English.. There were 127 students in the third grade and 25 were chosen as sample. The research method used was random sampling. The researcher employed a questionnaire to obtain the data using a non-test technique. Linear regression was the method of data analysis employed in this study, which was conducted using SPSS Version 23. The study's findings showed that the third grade pupils' motivation to learn English was fair (0.637), depending on the teacher's personality. It showed that the motivation of the pupils increased with the personality of the teacher. The likelihood is 0.004. This indicates that the hypothesis is plausible. As a result, it can be said that the personality of the teacher has a considerable impact on how motivated the third-grade pupils at SMPN 3 Pallangga are to learn English.